Bioactive compounds of citrus as health promoters - Duarte, Amílcar (2016)
Citrus are a group of fruit species, quite heterogeneous in many aspects, including chemical composition of the fruit. Since ancient times, some citrus fruits were used to prevent and cure human diseases. In the recent decades, it has been demonstrated that fruits can actually help prevent and cure some diseases and above all, they are essential in a balanced diet. Citrus fruits, as one of the groups of fruit species, with greater importance in the world, have been studied for their effects on human health. Some species of citrus were referred as potential antioxidant based therapy for heart disease, cancer and inflammation. Fruit peels and seeds have also high antioxidant activity. The health benefits of citrus fruit have mainly been attributed to the high level of bioactive compounds, such as phenols (e.g., flavanone glycosides, hydroxycinnamic acids), carotenoids and vitamin C. These compounds are present in the fruit pulp and hence in the juice. But some bioactive compounds can be found in parts of the fruit which usually are not used for human food. The content of bioactive compounds depends on the species and cultivar, but also depends on the production system followed in the orchard. Citrus fruits, their derivatives and their by-products (peel, pulp and oil) are reach in different bioactive compounds and its maturity, postharvest and agroindustry processes influence their composition and concentration. The aim of this chapter was to review the main bioactive compounds of the different components of citrus and their relationship to health.